Analisis Strategi Pemasaran dan Harga Terhadap Volume Penjualan di PT. Pandum Parahita Lestantum - Kristiani Lidia Telaumbanua; Kamil, Musthafa (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This research aims to determine the effect of marketing strategy and price on sales volume at PT. Pandum Parahita Lestantum both partially and simultaneously. The method used in this research is a quantitative approach. The research sample consisted of 100 people taken using saturated sampling. With data collection techniques using a questionnaire in the form of a Likert scale. Data analysis was carried out using data quality analysis techniques, classical assumptions, hypotheses, which were processed using SPSS (Statistical Package for the Social Sciences) software version 25. The research results showed that from the results of research hypothesis testing there was an unsupported and partially significant influence between the strategies. marketing to sales volume.